Validity and reliability of the Korean version of the gender-friendliness barriers in nursing programs scale - Park, Seon-Min; Kim, Jung-Hee (Frontiers in Psychology, 2023)
Introduction The gender-friendliness barriers in nursing programs (GFB-NP) were used to measure perceived gender affinity among male nursing students in nursing education programs. Originally developed in Taiwan, this scale has not been used in Korea. The purpose of this study is to confirm the reliability and validity of the GFB-NP scale for Korean male nursing students. Methods A convenience sample of male nursing students enrolled in the 1st to 4th year of nursing departments at five four-year universities located in three cities in Korea was used in the study. To confirm the validity and factor structure of the scale, both exploratory factor analysis and confirmatory factor analysis were employed. Results The results support a four-factor structure: Professional acquisition opportunity, peer interaction, sociocultural prejudice, and gender role attitude. We confirmed that the Korean version of the GFB-NP is an appropriate tool for measuring the gender-friendliness educational environment perceived by male nursing students in nursing education. Discussion The GFB-NP will serve as a framework for developing counseling and management strategies to help male nursing students successfully adapt to school life within the nursing education curriculum. Research with a longitudinal study design is recommended to investigate the progression of school adaptation through undergraduate program courses.